Fetus with Lateral Gastroschisis Born to a Celiac Mother - Kaushaki Shankar; Parveen Kumar; Ashish Jain; Abhishek Chopra (EL-Med-Pub, 2019)
Gastroschisis is a rare anterior abdominal wall defect which develops secondary to an early embryonic vascular defect. We report here a rare site of gastroschisis involving the posterior aspect of lateral abdominal wall on the right side, born to a celiac mother. There is no reported literature on any association between gastroschisis and celiac disease. We propose here possible role of palmitic acid pathway in this index case.